Where Was the Working Class? Revolution in Eastern Germany - Buse, Dieter K. (Labour / Le Travail, 2002)
The article reviews the book, "Where was the working class? Revolution in Eastern Germany," by Linda Fuller.
Keywords: Business And Economics–Labor And Industrial Relations; History; History–History of North And South America; Working class